2018
DOI: 10.1371/journal.pbio.2006519
|View full text |Cite
|
Sign up to set email alerts
|

Copper-dependent amino oxidase 3 governs selection of metabolic fuels in adipocytes

Abstract: Copper (Cu) has emerged as an important modifier of body lipid metabolism. However, how Cu contributes to the physiology of fat cells remains largely unknown. We found that adipocytes require Cu to establish a balance between main metabolic fuels. Differentiating adipocytes increase their Cu uptake along with the ATP7A-dependent transport of Cu into the secretory pathway to activate a highly up-regulated amino-oxidase copper-containing 3 (AOC3)/semicarbazide-sensitive amine oxidase (SSAO); in vivo, the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 50 publications
(54 reference statements)
2
48
0
Order By: Relevance
“…In a mouse model of hereditary copper imbalance, copper have been shown to be an endogenous regulator of lipolysis (Krishnamoorthy et al, 2016). Copper deficiency can significantly increase plasma cholesterol, which can also lead to fat cell hypertrophy and fat accumulation (Yang et al, 2018). Therefore, copper might be used as a dietary supplement.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of hereditary copper imbalance, copper have been shown to be an endogenous regulator of lipolysis (Krishnamoorthy et al, 2016). Copper deficiency can significantly increase plasma cholesterol, which can also lead to fat cell hypertrophy and fat accumulation (Yang et al, 2018). Therefore, copper might be used as a dietary supplement.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a negative correlation with the subscapular skinfold and fat mass. Recently, Cu has emerged as an important modifier of body lipids; a deficiency of Cu causes the inhibition of semicarbazide-sensitive amine oxidase (SSAO) activity-a regulatory enzyme of energy utilization processes in adipocytes that favors adipocyte hypertrophy and fat deposition [35]. It is thus necessary to check this TE in runners, because excess fat mass is negatively related to sport performance [1] Li plays an important role in several physiological functions-neural communication, metabolism and cell proliferation-but a deficit or excess concentrations induce negative or toxic effects [36].…”
Section: Discussionmentioning
confidence: 99%
“…Cu is known to influence tumor growth through the stimulation of several cuproenzymes, including Ceruloplasmin (CP), MEK1/2, and Cytochrome C Oxidase (CCO/COX), which are associated with various biological functions [30][31][32][33] . To stimulate these cuproenzymes, Cu is loaded in the secretory pathway via a process that is dependent on ATP7A [34][35][36][37] . Strikingly, we found that ATP7A knockdown significantly increased CCS levels in KRAS IEC-6 cells ( Fig.…”
Section: Kras G12vmentioning
confidence: 99%